Age Dependent Cost-Effectiveness of Cochlear Implantation in Adults. Is There an Age Related Cut-off?. Issue 7 (August 2019) - Laske, Roman D.; Dreyfuss, Michael; Stulman, Alan; Veraguth, Dorothe; Huber, Alexander M.; Röösli, Christof
Abstract : Objective: To analyze the impact of age at implantation on the cost-effectiveness of cochlear implantation (CI). Study Design: Cost-utility analysis in an adapted Markov model. Setting: Adults with profound postlingual hearing loss in a "high income" country. Intervention: Unilateral and sequential CI were compared with hearing aids (HA). Main Outcome Measure: Incremental cost-effectiveness ratio (ICER), calculated as costs per quality adjusted life year (QALY) gained (in CHF/QALY), for individual age and sex combinations in relation to two different willingness to pay thresholds. 1 CHF (Swiss franc) is equivalent to 1.01 USD. Results: When a threshold of 50, 000 CHF per QALY is applied, unilateral CI in comparison to HA is cost-effective up to an age of 91 for women and 89 for men. Sequential CI in comparison to HA is cost-effective up to an age of 87 for women and 85 for men. If a more contemporary threshold of 100, 000 CHF per QALY is applied, sequential CI in comparison to unilateral CI is cost-effective up to an age of 80 for women and 78 for men. Conclusions: Performing both sequential and unilateral CI is cost-effective up to very advanced ages when compared with hearing aids.